2017
DOI: 10.1002/jum.14292
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Validity Evidence for Simulation‐Based Assessment of Point‐of‐Care Ultrasound Skills

Abstract: The performance of FAST examinations can be assessed in a simulated setting using defensible performance standards, which have both good reliability and validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In this light, e‐learning provides an opportunity to expose learners to an image interpretation learning experience (i.e., part‐task) that could complement the resource intensive face‐to‐face teaching and learning at the bedside that addresses all facets of POCUS (i.e., whole‐task) . However, to date, most POCUS simulation and online education focuses on image acquisition, specific conditions (e.g., cardiac tamponade), or adult applications . As such, existing teaching tools are limited in being able to significantly improve learner exposure to the part‐task of pediatric POCUS image interpretation.…”
mentioning
confidence: 99%
“…In this light, e‐learning provides an opportunity to expose learners to an image interpretation learning experience (i.e., part‐task) that could complement the resource intensive face‐to‐face teaching and learning at the bedside that addresses all facets of POCUS (i.e., whole‐task) . However, to date, most POCUS simulation and online education focuses on image acquisition, specific conditions (e.g., cardiac tamponade), or adult applications . As such, existing teaching tools are limited in being able to significantly improve learner exposure to the part‐task of pediatric POCUS image interpretation.…”
mentioning
confidence: 99%
“…Future studies could assess the time and number of attempts the novices need to reach the pass/fail level and to compare this to the number of attempts and time needed to reach the learning curve plateau. This will highlight whether novices acquire additional learning beyond the pass/fail level, as previous studies have suggested [33, 34]. …”
Section: Discussionmentioning
confidence: 88%
“…Previous studies show that there is a difference between pass/fail level and learning curve plateau, indicating that the trainees might be proficiently trained when reaching the pass/fail level, but still have potential to reach a higher level of competence until reaching a learning curve plateau [30, 33, 34]. When reaching the learning curve plateau the trainees would not benefit from further simulation training.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have gathered validity evidence for a practical test in LUS, even though there has been an increased focus on the use of ultrasound for thoracic assessment, including the accuracy and eligibility of LUS [28]. Assessment tools for the evaluation of ultrasound skills in other organ systems have been published within the last decade [29-32]. …”
Section: Discussionmentioning
confidence: 99%